2004
DOI: 10.1186/1471-2334-4-49
|View full text |Cite
|
Sign up to set email alerts
|

A national survey of the prevalence of schistosomiasis and soil transmitted helminths in Malaŵi

Abstract: Background: Past estimates have put the prevalence of schistosomiasis between 40% and 50% in the Malawi population overall based on studies undertaken ten years or more ago. More recent surveys in known high risk areas find similar levels. However control measures, changing ecology and migration may have led to changes in the prevalence of schistosomiasis in different parts of Malawi. A national schistosomiasis and soil-transmitted helminth (STH) survey was undertaken to measure the distribution, prevalence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
59
3
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 9 publications
13
59
3
1
Order By: Relevance
“…This may be due to differences in exposure (due to behavioural differences, particularly with respect to water contact), physiological changes at puberty leading to lower susceptibility (including interactions between hormonal, anatomical and immunological changes), and the development of acquired immunity (Feldmeier et al 1998;Fulford et al 1998;Mutapi et al 2006). Higher prevalence and intensity of infection has been reported in males than females (Ansell et al 2001;Ndyomugyenyi & Minjas 2001;Bowie et al 2004), though exceptions have also been reported (Mafe et al 2000). For S. haematobium and S. mansoni (which has similar age-gender patterns), different immune responses between the sexes have been argued to be an important contributor to observed differences in intensity of infection (Marguerite et al 1999;Remoué et al 2001).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This may be due to differences in exposure (due to behavioural differences, particularly with respect to water contact), physiological changes at puberty leading to lower susceptibility (including interactions between hormonal, anatomical and immunological changes), and the development of acquired immunity (Feldmeier et al 1998;Fulford et al 1998;Mutapi et al 2006). Higher prevalence and intensity of infection has been reported in males than females (Ansell et al 2001;Ndyomugyenyi & Minjas 2001;Bowie et al 2004), though exceptions have also been reported (Mafe et al 2000). For S. haematobium and S. mansoni (which has similar age-gender patterns), different immune responses between the sexes have been argued to be an important contributor to observed differences in intensity of infection (Marguerite et al 1999;Remoué et al 2001).…”
Section: Introductionmentioning
confidence: 94%
“…Population age profiles among schoolaged children (as defined by parasitological field surveys) typically show an increase in prevalence and intensity of infection from the youngest age groups to the early teens, and often a subsequent decline in the mid to late teens (Booth et al 1998;Ndyomugyenyi & Minjas 2001;Bowie et al 2004;Clennon et al 2004). This may be due to differences in exposure (due to behavioural differences, particularly with respect to water contact), physiological changes at puberty leading to lower susceptibility (including interactions between hormonal, anatomical and immunological changes), and the development of acquired immunity (Feldmeier et al 1998;Fulford et al 1998;Mutapi et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This questionnaire was generating with the guidance of WHO guidelines and previous similar studies. 7,11 Specimen collection and parasitological analysis…”
Section: Data Collectionmentioning
confidence: 99%
“…5 A 1996 study that assessed resident expatriates in Malawi who had visited the lake found a prevalence of 33%. 6 Although the 2002 National Survey on Schistosomiasis and Soil-transmitted Helminths found a national schistosomiasis prevalence of 6.9%, 7 and a 2006 Blantyre study found a prevalence of 10.4% among school children, 8 high prevalence rates persist in communities along Lake Malawi, especially along the southern part. A Nankumba Peninsula study among school children in lakeshore villages found a schistosomiasis prevalence of 36.5% in 2003, and 23.7% in 2007, with reinfection rates of 30% to 40%, a year after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] Estimates of its prevalence vary across Malawi, 17 with some estimates suggesting that 40% to 50% of Malawians are infected. 2,9,18 It has been suggested that these estimates were derived from studies conducted too long ago (in the 1990s) to be valid now, and that they were skewed by a selection bias for high-risk areas. 2,9 This suggests that more up-to-date local estimates would be more helpful for planning of control strategies.…”
Section: Introductionmentioning
confidence: 99%